The Challenges of the Digital Divide in ASEAN and Its Impact on Digital Business Acceleration - Muslimin, Muslimin; Naim, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
This study examines the dynamics of digital transformation and the persistent digital divide across ASEAN countries, focusing on the impact of digital infrastructure and policy readiness on inclusive economic growth. Using a qualitative descriptive approach through secondary data analysis from academic publications (2019–2024) and international institutional reports, this research integrates statistical data from the ASEAN Secretariat, ITU, and World Bank to reveal varying levels of connectivity and digital literacy. The findings indicate that although digital adoption in ASEAN has accelerated, disparities in infrastructure quality, policy alignment, and human capital remain significant. The study concludes that strengthening regional cooperation, harmonizing digital policies, and investing in equitable access are essential to achieving a more inclusive and resilient digital economy in Southeast Asia